Emergency department falls: a longitudinal analysis of revisits and hospitalisations between patients who fall and patients who did not fall. Issue 12 (10th December 2020) - Shankar, Kalpana N; Lin, Feng; Epino, Henry; Temin, Elizabeth; Liu, Shan
Abstract : Objective: Older adult falls are a national issue comprising 3 million emergency department (ED) visits and significant mortality. We sought to understand whether ED revisits and hospitalisations for fallers differed from non-fall patients through a secondary analysis of a longitudinal, statewide cohort of patients. Design: We performed a secondary analysis using the non-public Patient Discharge Database and the ED data from the California Office of Statewide Health Planning and Development. This is a 5-year, longitudinal observational dataset, which was used to assess outcomes for fallers and non-fall patients, defined as anyone who did not carry a fall diagnosis during this time period. Setting: 2005–2010 non-public Patient Discharge Database and the ED Data from the state of California. Participants: Older adults 65 years and older Main outcome measure: ED revisits and hospitalisations for fallers and non-fall patients. Results: Patients who came to the ED with an index visit of a fall were more likely to be discharged home after their fall (61.1% vs 45.0%, p<0.001). Fallers who were discharged or hospitalised after their index visit were more likely to come back to the ED for a fall related complaint compared with non-fallers (median time: 151 days vs 352 days, p<0.001 and hospitalised: 45 days vs 119 days, p<0.01) and fallers who were initially discharged also returned to the ED sooner for a non-fall related complaint (median time: 325 days vs 352 days, p<0.001). Conclusion: Fall patients tend to be discharged home more often after their index visit, but returned to the ED sooner compared with their non-fall counterparts. Given a faller's rates of ED revisits and hospitalisations, EDs should consider a fall as a poor prognostic indicator for future healthcare utilisation.